METHODS OF DRAWING FREELY AS AN EFFORT TO ENHANCE THE CHILD’S CREATIVITY IN ART LEARNING: METODE DALAM MENGGAMBAR BEBAS SEBAGAI UPAYA MENINGKATKAN KREATIVITAS ANAK DALAM PEMBELAJARAN SENI RUPA - Gussantoko, Galuh; Subiyantoro, Slamet; Widiastuti, Endang (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
In the present era art learning is still less given to children that resulted in lack of creativity owned by the child. With this lack of creativity, the child will not be confident to do something. In addition, creativity that is honed early on will also have a positive impact on the future human resources. In line with the development of science has made an influence in the development sector in the child's self-esteem especially creativity to create creative and innovative human beings in the future. So it takes coaching and guidance to keep the child's creativity in accordance with the talent of creativity that exists in the child. The goal to be achieved in this discussion is to increase the creativity of the child through the study of free drawing arts. The research uses a qualitative and descriptive methodology by utilizing documentation, a library study in the form of research journals to compile relevant information in relation to the issues studied. Keywords: Learning, visual arts, children, creativity